Nested nationalism : making and unmaking nations in the Soviet Caucasus - Goff, Krista A. (Cornell University Press, 2020)
"This book explores the politics and practices of managing national minority identifications, rights, and communities in the Soviet Union, and the consequences of such efforts. Drawing on archival and oral history research conducted in Armenia, Azerbaijan, Georgia, and Russia (Dagestan and Moscow), it examines Soviet nation-building, belonging, and citizenship, as well as broader questions about historical memory"--